Paylater Lifestyle: Financial Solution or Debt Trap for the Younger Generation - Adrian Eka Darma Serang; Adhis Darussalam Pamungkas; Tiara Nirmala (Nomico, 2025)
Paylater services have grown rapidly in Indonesia along with the increasing penetration of digital and e-commerce. Ease of access and more flexible requirements make it the main choice for the younger generation to meet consumer needs. However, uncontrolled use of Paylater can pose financial risks, such as debt accumulation, declining credit scores, and inhibiting the ability to save. The younger generation, who are still in the stage of building personal finances, are very vulnerable to these negative impacts. Studies show that most Paylater users are aged 20-30 years, with the majority using this service for online shopping and lifestyle. Dependence on Paylater reflects a weak awareness of long-term financial consequences. Without a good understanding of the fee and interest structure, many users are trapped in debt that is difficult to repay. This phenomenon is exacerbated by a culture of impulsive consumption driven by aggressive marketing strategies from e-commerce platforms. If not balanced with adequate financial literacy and strict regulations, Paylater risks exacerbating individual financial crises. Therefore, increasing financial literacy and stricter policies are urgently needed to ensure responsible use of Paylater, as well as to protect consumers and the stability of the financial sector.